A new species of Hirudo (Annelida: Hirudinidae): historical biogeography of Eurasian medicinal leeches - Saglam, Naim; Saunders, Ralph; Lang, Shirley A.; Shain, Daniel H. (Bmc, 2016)
Background: Species of Hirudo are used extensively for medicinal purposes, but are currently listed as endangered due to population declines from economic utilization and environmental pollution. In total, five species of Hirudo are currently described throughout Eurasia, with Turkey being one of the major exporters of medicinal leech, primarily H. verbana. Results: To define the distribution of Hirudo spp. within Turkey, we collected 18 individuals from six populations throughout the country. Morphological characters were scored after dorsal and ventral dissections, and Maximum Likelihood (ML) and Bayesian Inference (BI) analyses resolved phylogenetic relationships using mitochondrial cytochrome c oxidase subunit I (COI), 12S ribosomal RNA (rRNA), and nuclear 18S rRNA gene fragments. Our results identify a new species of medicinal leech, Hirudo sulukii n. sp, in Kara Lake of Adiyaman, Suluklu Lake of Gaziantep and Segirkan wetland of Batman in Turkey. Phylogenetic divergence (e.g., 10-14 % at COI), its relatively small size, unique dorsal and ventral pigmentation patterns, and internal anatomy (e.g., small and pointed atrium, medium-sized epididymis, relatively long tubular and arc formed vagina) distinguish H. sulukii n. sp. from previously described Hirudo sp. Conclusions: By ML and BI analyses, H. sulukii n. sp. forms a basal evolutionary branch of Eurasian medicinal leeches. Phylogeographic interpretations of the genus identify a European Hirudo explosion during the upper Miocene followed by geological events (e.g., Zanclean flood, mountain building) that likely contributed to range restrictions and regional speciation of extant members of the clade.
Keywords: Molecular Systematics; Oligochaeta; Phylogeography; Clitellata; Phylogeny; Selection; Accurate; Model; L.